STUDY OF FULLY-MIXED HYBRID THERMAL ENERGY STORAGE WITH PHASE CHANGE MATERIALS FOR SOLAR HEATING APPLICATIONS - Abdelsalam, Mohamed (My University, 2017)
A novel design of hybrid thermal energy storage (HTES) using Phase Change Material (PCM) was evaluated using a mathematical model. Both single and multi-tank (cascaded) storage were explored to span small to large-scale applications (200-1600 litres). The storage element was based on the concept of a fully-mixed modular tank which is charged and discharged indirectly using two immersed coil heat exchangers situated at the bottom and top of the tank. A three-node model was developed to simulate different thermal behaviors during the operation of the storage element. Experiments were conducted on full-scale 200-l single-tank sensible heat storage (SHS) and hybrid thermal energy storage (HTES) to provide validation for the mathematical model. The HTES incorporated rectangular PCM modules submerged in the water tank. Satisfactory agreement was found between the numerical results and the experimental results obtained by Mather (2000) on single and multi-tank SHS. In addition, good agreement was noticed with the experiments performed by the author on single-tank SHS and HTES at McMaster University. The developed model was found to provide high levels of accuracy in simulating different operation conditions of the proposed design of storage element as well as computational efficiency. A parametric study was undertaken to investigate the potential benefits of the HTES over the SHS, operating under idealistic conditions. The HTES can perform at least two times better than the SHS with the same volume. The PCM volume fraction, melting temperature and properties were found to have critical impact on the storage gains of the HTES. All the parameters must be adjusted such that: (1) the thermal resistance of the storage element is minimized, and (2) most of the energy exchange with the storage element takes place in the latent heat form. The performance of the single-tank HTES was evaluated numerically while operating in a solar thermal domestic hot water (DHW) system for a single-family residence. The PCM parameters were selected to maximize the solar fraction during the operation on a typical spring day in Toronto. The use of the HTES can reduce the tank volume by 50% compared to the matched size of the SHS tank. However, the HTES was found to underperform the SHS when the system was operated in different days with different solar irradiation intensities. The effect of different draw patterns was also investigated. The results indicated that thermal storage is needed only when the energy demand is out-of-phase with the energy supply. For the same daily hot water demand, different consumption profiles; ex. dominant morning, dominant evening, dominant night and dispersed consumptions, showed slight impact on the performance of the system. The concept of multi-tank (cascaded) HTES storage was explored for medium/large scale solar heating applications such as for restaurants, motels, and multi-family residences. The design was based on the series connection of modular tanks through the bottom and top heat exchangers. Each individual tank had a PCM with different melting temperature. The results showed that the cascaded storage system outperformed the single-tank system with the same total volume as a result of the high levels of sequential or tank-to-tank stratification. The use of the cascaded HTES resulted in slight improvement in the solar fraction of the system.
Keywords: Thermal Energy Storage; Phase Change Materials; Solar Heating; Cascaded Storage